Community-set goals are needed to increase diversity in language acquisition research: A commentary on Kidd and Garcia (2022). Issue 6 (December 2022) - Havron, Naomi; Scaff, Camila; Hitczenko, Kasia; Cristia, Alejandrina
This commentary argues that to increase diversity in language acquisition research, the field should define specific, measurable, attainable, relevant, and time-defined goals, and prioritize solutions based on their importance, tractability, and neglectedness, ideally in collaboration with a variety of other agents outside the research community.